If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + -1(2x + 9)) = -4 + -1(6(2x + -4) + -6x) Reorder the terms: -1(6x + -1(9 + 2x)) = -4 + -1(6(2x + -4) + -6x) -1(6x + (9 * -1 + 2x * -1)) = -4 + -1(6(2x + -4) + -6x) -1(6x + (-9 + -2x)) = -4 + -1(6(2x + -4) + -6x) Reorder the terms: -1(-9 + 6x + -2x) = -4 + -1(6(2x + -4) + -6x) Combine like terms: 6x + -2x = 4x -1(-9 + 4x) = -4 + -1(6(2x + -4) + -6x) (-9 * -1 + 4x * -1) = -4 + -1(6(2x + -4) + -6x) (9 + -4x) = -4 + -1(6(2x + -4) + -6x) Reorder the terms: 9 + -4x = -4 + -1(6(-4 + 2x) + -6x) 9 + -4x = -4 + -1((-4 * 6 + 2x * 6) + -6x) 9 + -4x = -4 + -1((-24 + 12x) + -6x) Combine like terms: 12x + -6x = 6x 9 + -4x = -4 + -1(-24 + 6x) 9 + -4x = -4 + (-24 * -1 + 6x * -1) 9 + -4x = -4 + (24 + -6x) Combine like terms: -4 + 24 = 20 9 + -4x = 20 + -6x Solving 9 + -4x = 20 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -4x + 6x = 20 + -6x + 6x Combine like terms: -4x + 6x = 2x 9 + 2x = 20 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 2x = 20 + 0 9 + 2x = 20 Add '-9' to each side of the equation. 9 + -9 + 2x = 20 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 20 + -9 2x = 20 + -9 Combine like terms: 20 + -9 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| 7(5+y)= | | 25/60=5/15 | | 1.2x+3.8=8.696 | | 4(c-9)=-24 | | Q=1640-20p | | 10x+9=2x+25 | | 37x+5=y | | q+72=36 | | -y=5x+7 | | 2/5x-12/5 | | x+2x+3x-3-8=6x-11 | | 5(3h+-2)=2(h+8) | | -108+72=36 | | 110=(5a+6a) | | X-18=11x-38 | | 8(6u+5)= | | 6(2+a)=-18 | | 45=9q | | 25x^9/5x^8 | | x+y+z+t+u=7 | | 5(9+7y)= | | x+y+z+t=5 | | 35+25=40x | | -5(x/100-5x)=-2 | | 32f+26f=232 | | 45/x=18 | | 15c-6=24 | | 140=0.66666666666667c | | 5+[30-(6-1)]= | | Y=2x+2(x+1)+6 | | 33n+63= | | 140=.66666666666667 |